Paleomagnetism of the ~860 Ma Manso dyke swarm, West Africa: implications for the assembly of Rodinia - Antonio, Paul Yves Jean (2021)
The West African Craton (WAC) is one of the major cratons in the Rodinia jigsaw puzzle (~1000?750Ma). In the Rodinian models, the position of West Africa is mainly constrained by the assumptionthat it had been a partner of Amazonia since the Paleoproterozoic. Unfortunately, nopaleomagnetic data are available for these cratons when the Rodina supercontinent is consideredtectonically stable (~1000-750 Ma). Thus, every new reliable paleomagnetic pole for the WestAfrican Craton during the Neoproterozoic times is of paramount importance to constrain itsposition and testing the Rodinia models. In this study we present a combined paleomagnetic andgeochronological investigation for the Manso dyke swarm in the Leo-Man Shield, southern WestAfrica (Ghana). The ~860 Ma emplacement age for the NNW-trending Manso dykes is thus wellconstrainedby two new U-Pb apatite ages of 857.2 ± 8.5 Ma and 855 ± 16 Ma, in agreement withbaddeleyite data. Remanence of these coarse-to-fine grained dolerite dykes is carried by stablesingle to pseudo-single domain (SD-PSD) magnetite. A positive baked-contact test, associated to apositive reversal test (Class-C), support the primary remanence obtained for these dykes (13 sites).Moreover, our new paleomagnetic dataset satisfy all the seven R-criteria (R=7). The ~860 MaManso pole can thus be considered as the first key Tonian paleomagnetic pole for West Africa. Wepropose that the West Africa-Baltica-Amazonia-Congo-São Francisco were associated in a longlivedWABAMGO juxtaposition (~1100?800 Ma).